2021
DOI: 10.1111/cei.13647
|View full text |Cite
|
Sign up to set email alerts
|

Follicular helper and follicular regulatory T cell subset imbalance is associated with higher activated B cells and abnormal autoantibody production in primary anti-phospholipid syndrome patients

Abstract: Primary anti-phospholipid antibody syndrome (pAPS) is a multi-organ autoimmune disease, and autoantibodies are involved in its pathogenesis. Follicular helper T cells (Tfh) and follicular regulatory T cells (Tfr) are critical for B cell maturation and antibody production, but their roles in pAPS remain unknown. We enrolled 32 pAPS patients and 23 healthy controls (HCs) and comprehensively analyzed circulating Tfh and Tfr, as well as their subsets, using flow cytometry. Clinical data including autoantibody leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
2
6
0
1
Order By: Relevance
“…Transitional (CD24+CD38+) and double negative (CD27-IgD-) B-cells were found to be increased [33,43] or unaltered [34] in patients with PAPS and interleukin-10 producing regulatory B-cells (Bregs) were found decreased in patients with PAPS [42]. Transitional B-cells may develop into naïve B-cells, an increase in these cells may therefore be in line with the increase in naïve B-cells reported by others as outlined earlier.…”
Section: Alterations Of Transitional Double Negative and Regulatory B...supporting
confidence: 86%
See 2 more Smart Citations
“…Transitional (CD24+CD38+) and double negative (CD27-IgD-) B-cells were found to be increased [33,43] or unaltered [34] in patients with PAPS and interleukin-10 producing regulatory B-cells (Bregs) were found decreased in patients with PAPS [42]. Transitional B-cells may develop into naïve B-cells, an increase in these cells may therefore be in line with the increase in naïve B-cells reported by others as outlined earlier.…”
Section: Alterations Of Transitional Double Negative and Regulatory B...supporting
confidence: 86%
“…Three studies measured the frequency of plasmablasts in the peripheral blood of patients with PAPS of which two reported an increase [42,43] and the other no statistically significant difference [34] in the number of plasmablasts between patients with PAPS versus healthy controls, although a similar trend was seen in this latter study. In one study, plasmablasts were identified as producers of aPL since omitting plasmablasts (by depletion of CD20 negative B-cells) from peripheral blood mononuclear cells from patients with PAPS that were stimulated ex vivo with IL-6, IL-21, CD40L, and APRIL resulted in an abrogation of the production of aPL.…”
Section: Plasmablasts Are Increased In Patients With Paps and May Be ...supporting
confidence: 56%
See 1 more Smart Citation
“…Tfr cells represent a specialized subpopulation of Tfh cells with signatures from Treg and are present in B cell follicles. Accumulating evidence has highlighted a heterogeneity of Tfr cells in humans and mice, 35–37 of which Tfr (CD4 + CXCR5 + CD45RA low Foxp3 + ) cells with IL‐10‐deficient secretion have been shown to be inadequate in suppressing memory B cells in AR patients 38,39 …”
Section: Pathomechanisms In Armentioning
confidence: 99%
“…34 Tfr cells represent a specialized subpopulation of Tfh cells with signatures from Treg and are present in B cell follicles. Accumulating evidence has highlighted a heterogeneity of Tfr cells in humans and mice, [35][36][37] of which Tfr (CD4 + CXCR5 + CD45RA low Foxp3 + ) cells with IL-10-deficient secretion have been shown to be inadequate in suppressing memory B cells in AR patients. 38,39 Restoring Treg function in AR is one of the therapeutic targets, which is mainly dependent on the regulation of FOXP3 and inhibitory cytokines such as IL-10 and transforming growth factorβ (TGFβ).…”
Section: T Cell Subsets In Armentioning
confidence: 99%